2021
DOI: 10.1002/edm2.267
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of sex hormone‐binding globulin, total testosterone, androstenedione and free testosterone with metabolic and reproductive features of polycystic ovary syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that FAI and androstenedione are associated with MS in PCOS 17–21 . In this work, we showed that these two androgens are independently related to siMS in women with PCOS and thus, could contribute to MS in PCOS through different pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have shown that FAI and androstenedione are associated with MS in PCOS 17–21 . In this work, we showed that these two androgens are independently related to siMS in women with PCOS and thus, could contribute to MS in PCOS through different pathophysiological pathways.…”
Section: Discussionsupporting
confidence: 60%
“…However, a study that excluded all abnormal BMIs when selecting study participants reported a free T value significantly lower than the other literature values and the subreddit value [ 35 ]. It has been reported in several PCOS studies that elevated free androgens are strongly associated with elevated BMI [ 47 - 49 ]. Thus, it is logical that the only study to exclude patients with an abnormal BMI is the only one to report a significantly lower free T value.…”
Section: Discussionmentioning
confidence: 99%
“…The larger studies reported higher SHBG values than the subreddit values, but the normal BMI study found a lower SHBG value. SHBG levels are lower in populations with PCOS [ 50 ], but this is especially true in those who also possess a high BMI [ 47 - 49 ]. Since the subreddit BMI was often lower than the literature values, it is expected that the subreddit SHBG would be higher than the literature values that did not exclude based on BMI but lower than the literature values that only took normal-BMI participants.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis also suggested that women with PCOS and lower SHBG levels were more likely to have hyperandrogenism, metabolic issues and infertility ( 118 ). SHBG levels are especially lower in those who also possess a high BMI ( 121 123 ). Figure 10 shows how SHBG is dysregulated in PCOS.…”
Section: Metabolic Hormone Changesmentioning
confidence: 99%